Beyond the Status of Health: A Collection of Stories Representing Diverse Maternal Mental Health Perspectives - Sara Santarossa; Ruth A. Blake; Heather Buchanan; Mercedes Price; Rachael Guzzardo; Craig Guzzardo; LaKenya M. Johnson; Jacobeth M. Morshall; Andrea Bate; Wayne Bate; Riziki Bakari; Leah Copeland; et al. (Journal of Patient-Centered Research and Reviews)
As part of a Patient-Centered Outcomes Research Institute (PCORI) Eugene Washington Engagement Award aimed at improving capacity to address maternal mental health in research, this collection of eight stories describes the unique experiences from caregivers (N = 2), patient/caregiver dyads (N = 2), healthcare stakeholders (N = 2), and community stakeholders (N = 2). Shared here are narratives dedicated to uplifting and supporting maternal mental health through storytelling. Elevating the voices and lived experiences of these diverse perspectives helps one understand the deeper and sometimes “invisible” needs of birthing people, thus moving beyond the status quo.